2017
DOI: 10.1111/nyas.13337
|View full text |Cite
|
Sign up to set email alerts
|

Claudin‐targeted drug development using anti‐claudin monoclonal antibodies to treat hepatitis and cancer

Abstract: The 27-member family of tetraspan membrane proteins known as claudins (CLDNs) is a major component of tight junctions. A series of studies elucidating the relationship between CLDNs and various pathological conditions has provided new insights into drug development. For instance, CLDN-1 may be a potent target for epidermal absorption of drugs and for treating hepatitis C virus (HCV) infection. CLDN-4 may be a target for treating cancer. Because CLDNs are also expressed in various normal tissues, safety and eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 90 publications
(203 reference statements)
0
18
0
1
Order By: Relevance
“…The tetraspanins are a family of four-pass transmembrane proteins that have both their N and C termini facing the cytosol. Tetraspanins are known to act as molecular scaffolds and have been implicated in several pathological conditions (e.g., cancer, infectious disease, inflammation, blindness; Hashimoto et al, 2017). Peripherin 2 (PRPH2 or peripherin/rds) is a photoreceptor-specific tetraspanin protein abundantly expressed in the cilium (outer segment) of both rods and cones.…”
Section: Introductionmentioning
confidence: 99%
“…The tetraspanins are a family of four-pass transmembrane proteins that have both their N and C termini facing the cytosol. Tetraspanins are known to act as molecular scaffolds and have been implicated in several pathological conditions (e.g., cancer, infectious disease, inflammation, blindness; Hashimoto et al, 2017). Peripherin 2 (PRPH2 or peripherin/rds) is a photoreceptor-specific tetraspanin protein abundantly expressed in the cilium (outer segment) of both rods and cones.…”
Section: Introductionmentioning
confidence: 99%
“…Claudin‐1 also stimulates the activation of pro‐matrix metalloproteinase‐2 to enhance invasiveness (Miyamori et al, ). Thus, targeting Claudin‐1 could potentially inhibit tumor metastasis (Hashimoto et al, ). Our study showed that β‐elemene downregulated Claudin‐1 mRNA and protein expression.…”
Section: Discussionmentioning
confidence: 99%
“…To elucidate the anti-metastasis mechanism of β-elemene in gastric cancer, RNA-seq was used to explore differentially expressed genes after β-elemene treatment. Claudin-1 has previously been identified as a potential target for anti-metastatic treatments (Cherradi et al, 2017;Hashimoto et al, 2017). Claudin-1 is a tight junction protein whose overexpression is seen in several cancers (de Oliveira et al, 2005;Eftang et al, 2013;Leotlela et al, 2007).…”
Section: However It Has Not Been Determined Whether Fak Regulatesmentioning
confidence: 99%
See 2 more Smart Citations